Respon Fisiologis Dan Serapan Hara Tanaman Jagung Terhadap Inokulasi Ganda Mikroba Dan Takaran Pupuk Urea Pada Media Gambut - Zulfita, Dwi; Surachman, Surachman; Budi, Setia; Rahmidiyani, Rahmidiyani; Hadijah, Siti (Faculty of Agriculture Universitas Singaperbangsa Karawang, 2023)
This study aims to determine the interaction between multiple inoculations of Arbuscular Mycorrhizae and non-symbiotic N-fixing bacteria Azosprrillum at different urea fertilizer dosages on physiological processes and N, P uptake in peat soils. The study used a factorial design of 4x4 completely randomized layout with 3 replications. The first factor is the inoculation of Arbuscular Mycorrhizae and Azospirillum lipoferum (M) consisting of 4 levels, namely m0 (without inoculation), m1 (Arbuscular mycorrhiza inoculation), m2 (Azospirillum lipoferum inoculation) and m3 (inoculation with Arbuscular Mycorrhiza and Azospirillum. lipoferum). The second factor is the dose of urea with 4 levels, namely n0 (without urea fertilizer), n1 (urea urea recommended dose), n2 (½ recommended dose) and n3 (recommended dose). The dose of urea for maize is 150 kg ha-1. The data obtained were analyzed statistically using analysis of variance (F test), if the F test showed a significant difference between each treatment and interaction, it was followed by Duncan's multiple distance test at the 5% level. Observations were made on N and P uptake, Net Assimilation Rate (LAB) and relative growth rate (LPN). The results showed that the double inoculation of Arbuscular Mycorrhizae and Azospirillum lipoferum was effective at all doses of urea in increasing nutrient uptake of N and P.